A Reconfigurable Ultra-Wideband (UWB) Antenna with Single Band-Rejection - Miswadi, NF.; Ali, M.T.; Aris, M.A.; Baba, N.H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this paper, a reconfigurable ultra-wideband (UWB) antenna with WLAN band-rejection is presented. The proposed antenna operates in the ultra-wideband frequency band from 2.99 – 10.82 GHz with band- rejection of 5.00 – 5.85 GHz. The structure of the antenna is simple octagon-shaped radiating patch and half ground plane with dimension of 30 x 40 mm2. Bandstop elements (inverted U-shaped slot) are integrated into the structure of the antenna to achieve WLAN bandrejection. Band-rejection reconfigurable capability are achieved by placing RF switches at the slot. By configuring the switch in the ON and OFF modes, two reconfigurable states are realized which are WLAN band-rejection during ON states and full UWB frequency spectrum during off states. The proposed antenna shows a wide impedance bandwidth with sharp rejection at the WLAN band and provide multi-function antenna due to its reconfigurable characteristics. The performance was analyzed in terms of reflection loss, VSWR, gain and radiation pattern. Simulation and measurement result have achieved a good agreement.